The conquest of American inflation - Sargent, Thomas J. (Princeton, N.J. : Princeton University Press, 1999)
This essay is about how policy makers in the united states learned to believe and act upon a version of the natural unemployment rate.
Includes bibliographical references (p. [137]-144) and indexes.
nmn, 22/07/16
Loan
Keywords: Inflation (Finance); Inflation -American; United States